2013
DOI: 10.1155/2013/270878
|View full text |Cite
|
Sign up to set email alerts
|

The Correlations of Disease Activity, Socioeconomic Status, Quality of Life, and Depression/Anxiety in Chinese Patients with Systemic Lupus Erythematosus

Abstract: The prevalence of psychological problems is frequent in systemic lupus erythematosus (SLE) patients and appears to be increasing. The current study investigated the relationship among disease parameters, quality of life, and the psychological status in Chinese patients with SLE. A self-report survey design was administered to 170 SLE patients and 210 healthy individuals using the Self-Rating Anxiety Scale, the Self-Rating Depression Scale, and the Short Form 36 health survey (SF-36). Our results showed that 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
1
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 26 publications
6
63
1
9
Order By: Relevance
“…A handful of studies reported higher depression prevalence in individuals with SLE as compared to those without SLE [119,121,127]. A few studies estimated the prevalence of depression at 13% [115] and 60% [117] among adults with SLE.…”
Section: Prevalence Of Depression Among Individuals With and Withomentioning
confidence: 99%
“…A handful of studies reported higher depression prevalence in individuals with SLE as compared to those without SLE [119,121,127]. A few studies estimated the prevalence of depression at 13% [115] and 60% [117] among adults with SLE.…”
Section: Prevalence Of Depression Among Individuals With and Withomentioning
confidence: 99%
“…12 With greater understanding of the interaction between pregnancy and SLE, as well as cooperation among physicians who provide care for such patients, the maternal and infant prognosis has greatly improved. 13,14 However, some patients still have a poor prognosis, or even die of worsening SLE.…”
Section: Discussionmentioning
confidence: 99%
“…O nível de escolaridade das nossas participantes foi baixo, o que coloca em alerta a rede de cuidado, posto que estudos, realizados com pacientes chineses acometidos pelo LES, encontraram correlação significativa entre baixa escolaridade e sintomas de ansiedade e depressão (Mok, Chan, Cheung, & Yip, 2014;Shen et al, 2013). A escolaridade também foi associada à maior atividade da doença (Pons-Estel et al, 2004) e a adesão ao tratamento (Maldaner, Beuter, Brondani, Budó & Pauletto, 2008).…”
Section: Discussionunclassified
“…Quanto a esse dado, pesquisas apontam que índices socioeconômicos baixos estão associados a pior estado da doença, elevada morbidez psiquiátrica e alta mortalidade (Lorant et al, 2003). Somado a isso, estudos também mostram que o baixo nível socioeconômico está associado a uma menor qualidade de vida (Shen et al, 2013), a alta atividade da doença (Alarcón et al, 2006) e relacionado a danos cumulativos (Pons-Estel et al, 2004).…”
Section: Discussionunclassified
See 1 more Smart Citation